Dual-Energy CT for Evaluation of Intra- and Extracapsular Silicone Implant Rupture - Katrina N. Glazebrook; Shuai Leng; Steven R. Jacobson; Cynthia M. McCollough (Case Reports in Radiology)
Silicone implants are commonly used for both breast augmentation and breast reconstruction. With aging of the implant, the silicone envelope may become weak or may rupture. The technique of choice for evaluation of implant integrity is breast MRI; however this may be contraindicated in some patients or the cost may be prohibitive. Dual-energy CT allows determination of density and atomic number of tissue and can provide material composition information. We present a case of extracapsular implant rupture with MRI and dual-energy CT imaging and surgical correlation.